IN PRAISE OF LUMPEN HUMANITY: AGGREGATION, PERSONAL & IMPERSONAL REASONS - Munoz-Dardé, Véronique (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2019)
T. M. Scanlon’s contractualism and more specifically his conception of morality narrowly conceived proscribe direct appeal to what he calls impersonal values, such as items of natural beauty or cultural goods. In the scope of what we owe to each other, one should appeal only to concerns arising from what bears directly on individuals, by reference to which they can reasonably reject one set of principles in favour of another. There is an overlooked ambiguity here in how we should understand the scope of “what we owe to each other.” Unpacking this helps us see more clearly how contractualism can respond to the challenge that it must accommodate the intuitive force of aggregating: that, when all other things are equal, we are required to save a greater number of people over a lesser. I explain the role personal and impersonal value have in Scanlon’s contractualism. I connect the focus on personal value with perspectivalism, the justificatory privileging of the perspective of victims. Perspectivalism, I suggest, is motivated by Scanlon’s constructivist methodology. Whether perspectivalism is adequate as the basis of contractualism is not independent of the question of aggregation. Given the ambiguity highlighted, I conclude that other forms of contractualism might safely ignore the demands of aggregation.